1984
DOI: 10.1111/j.1095-8649.1984.tb04892.x
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific differences in thermal tolerance of Etheostoma spectabile (Agassiz) in constant versus fluctuating environments

Abstract: The critical thermal maximum (CTM) of Efheosforna specfabile differed significantly among four populations whose habitats ranged from thermally constant to highly fluctuating conditions. Mean CTM of the population at the most fluctuating location was highest, populations in intermediate thermal environments were intermediate in thermal tolerance, and a population in a constant temperature spring run had thelowest CTM. The results support the view that thermal physiology a n be evolutionarily labile within a sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 23 publications
(31 reference statements)
5
34
0
Order By: Relevance
“…However, physiological eurotopy might not provide this advantage to populations occurring at the margins of a species range, where individuals may already be at the limits of their physiological tolerance ranges (see Tedengren and others 1988). The evidence for increased thermal tolerance for lotic fishes from more variable environments (e.g., Matthews and Styron 1981, Feminella and Matthews 1984, Matthews 1987 suggests that physiological homeostatic responses may indeed be more fully developed under increasing environmental variation in streams. Life history traits enhancing survival in variable environments have been observed for lotic insects (Siegfried and Knight 1977, Vepsfil~iinen 1978, Gray 1981 and for fish (John 1963, Harrell 1978, Matthews 1987, Schlosser 1987.…”
Section: Biotic Responses To Anthropogenic Disturbancesmentioning
confidence: 95%
See 1 more Smart Citation
“…However, physiological eurotopy might not provide this advantage to populations occurring at the margins of a species range, where individuals may already be at the limits of their physiological tolerance ranges (see Tedengren and others 1988). The evidence for increased thermal tolerance for lotic fishes from more variable environments (e.g., Matthews and Styron 1981, Feminella and Matthews 1984, Matthews 1987 suggests that physiological homeostatic responses may indeed be more fully developed under increasing environmental variation in streams. Life history traits enhancing survival in variable environments have been observed for lotic insects (Siegfried and Knight 1977, Vepsfil~iinen 1978, Gray 1981 and for fish (John 1963, Harrell 1978, Matthews 1987, Schlosser 1987.…”
Section: Biotic Responses To Anthropogenic Disturbancesmentioning
confidence: 95%
“…Martin and Gentry (1974) showed that dragonfly larvae could avoid lethal thermal conditions by migrating temporarily into the deeper, cooler substratum. Fish physiological tolerances have been found greater in thermally variable vs more constant environments both within and among species (Matthews and Styron 1981, Feminella and Matthews 1984, Matthews 1987. Matthews (1987) also showed that individuals from "harsh" environments were more adept than those from "benign" environments at finding the least stressful microhabitats as physicochemical conditions deteriorated.…”
Section: Rationale For Physical Habitat Template In Lotic Ecosystemsmentioning
confidence: 98%
“…CT max is defined as the upper temperature at which a fish loses the ability to escape conditions that will ultimately lead to its death (Cox, 1974;Becker and Genoway, 1979;Beitinger et al, 2000). Thermal tolerance is affected by multiple factors including genetic differences (Elliott, 1991), acclimation temperature (Becker and Genoway, 1979;Elliott, 1991) and exposure to fluctuating temperatures (Feminella and Matthews, 1984). Furthermore, the expression of HSPs has been implicated in thermal tolerance (Berger and Woodward, 1983;Fangue et al, 2006).…”
Section: Chronic Social Stress Impairs Thermal Tolerance In the Rainbmentioning
confidence: 99%
“…Resident populations of aquatic organisms which survive have adaptations (physiological, biochemical and/ or behavioral) to cope with these abiotic challenges. Objectives of several laboratory studies have included the determination of seasonal and/or die1 upper temperature tolerances of fish as a measure of physiological adaptation to changes in environmental temperature (Kowalski et al 1978, Paladino et al 1980, Lee & Rinne 1980, Feminella & Matthews 1984, Bulger 1984, Ingersoll & Claussen 1984, Bulger & Tremaine 1985, McClanahan et al 1986, Matthews 1987. Other studies have addressed the responses of fish to reduced dissolved oxygen concentrations (see review of Kramer 1987).…”
Section: Introductionmentioning
confidence: 99%